The Salmond Lecture - Simpson, AWB (Victoria University of Wellington Law Review, 2008)
In his lecture Professor Simpson places John Salmond's jurisprudential books, his First Principles of Jurisprudence and his Jurisprudence text book within both the context of the English text book tradition and the more specific context of the English tradition of the general jurisprudence book. Having pointed out that Salmond’s major text book was indeed written for students, Professor Simpson examines Salmond’s explanation of judicial reasoning and whether it can differentiated from other modes of thought. While ultimately Professor Simpson suggests that John Salmond's account of legal thought is not complete, he concludes that it can be favourably compared with other attempts to resolve the question. In particular, Professor Simpson contrasts John Salmond and his contemporaries’ efforts favourably with the efforts of the prominent Oxford legal philosopher HLA Hart. For his own part, Professor Simpson ultimately considers that perhaps there is not so much special about legal thinking when compared to other processes of rational decision making in everyday practical affairs.